The Russian-Ukrainian Invasion of Capital Markets in Southeast Asia Continues. - Muhammad Yusron; Puji Endah Purnamasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to investigate whether there are any abnormal changes in return, trading volume activity, and the variability of security returns prior to and during the time of the Russian-Ukrainian invasion. A total of eighty companies operating in the energy industry from Indonesia, Malaysia, Singapore, the Philippines, and Thailand make up the sample. The study utilizes secondary data from the financial statements of each individual financial institution. The purpose of this method is to determine whether there are changes in anomalous returns, trading volume activity, and security return variability between the time before the Russian-Ukrainian invasion and the time of the invasion. There are considerable disparities between the pre-event and post-event periods in Indonesia with regard to the level of trade activity that happened during both times. In addition, when it comes to testing the variability of security returns, there is a distinction between the pre-event and post-event periods in each of the five countries.